Does justice matter in voice? Inclusive leadership and employee voice: the moderating role of organizational justice perception - Qi, Lei; Xu, Yuping; Liu, Bing (Frontiers in Psychology, 2023)
Introduction: As a distinctive form of relational leadership, the impact of inclusive leadership on employee work behavior has been widely considered by scholars. The purpose of this study was to examine the positive effects of inclusive leadership on employee voice (promotive voice and prohibitive voice), and the moderating role of organizational justice perception (distributive justice, procedural justice, and interactional justice) on such positive effects. Methods: Based on social exchange theory, this study used a multi-wave and multi-source survey to obtain data from 258 subordinates and 52 team leaders from construction companies located in China. Results: The results showed that inclusive leadership was positively related to promotive voice and prohibitive voice. Distributive justice and interactional justice would strengthen the positive relationship between inclusive leadership and promotive voice. Distributive justice, procedural justice, and interactional justice would strengthen the positive relationship between inclusive leadership and prohibitive voice. Discussion: First, this study examined the impact of inclusive leadership on employee voice, emphasized the importance of inclusive leadership as the core of relational leadership, and provided guidance for improving employee promotive and prohibitive voice. Second, this study conceptualized organizational justice perception as distributive justice, procedural justice, and interactional justice, comprehensively considered the impact of the three dimensions of justice perception on the effectiveness of inclusive leadership, and provided specific reference for employee management practice from the perspective of justice.